The Small RNA RyhB Homologs from Salmonella Typhimurium Restrain the Intracellular Growth and Modulate the SPI-1 Gene Expression within RAW264.7 Macrophages - Diego Peñaloza; Lillian G. Acuña; M. José Barros; Paula Núñez; Fernanda Montt; Fernando Gil; Juan A. Fuentes; Iván L. Calderón (Microorganisms, 2021)
Growing evidence indicates that small noncoding RNAs (sRNAs) play important regulatory roles during bacterial infection. In Salmonella Typhimurium, several sRNAs are strongly up-regulated within macrophages, but little is known about their role during the infection process. Among these sRNAs, the well-characterized paralogs RyhB-1 and RyhB-2 are two regulators of gene expression mainly related with the response to iron availability. To investigate the role of the sRNAs RyhB-1 and RyhB-2 from S. Typhimurium in the infection of RAW264.7 macrophages, we analyzed several phenotypic traits from intracellular mutant strains lacking one and both sRNAs. Deletion of RyhB-1 and/or RyhB-2 resulted in increased intracellular survival and faster replication within macrophages. The bacterial metabolic status inside macrophages was also analyzed, revealing that all the mutant strains exhibited higher intracellular levels of ATP and lower NAD+/NADH ratios than the wild type. Expression analyses from bacteria infecting macrophages showed that RyhB-1 and RyhB-2 affect the intra-macrophage expression of bacterial genes associated with the Salmonella pathogenicity island 1 (SPI-1) and the type III secretion system (T3SS). With a two-plasmid system and compensatory mutations, we confirmed that RyhB-1 and RyhB-2 directly interact with the mRNAs of the invasion chaperone SicA and the regulatory protein RtsB. Altogether, these results indicate that the RyhB homologs contribute to the S. Typhimurium virulence modulation inside macrophages by reducing the intracellular growth and down-regulating the SPI-1 gene expression.